Acupuncture modulates the gut microbiota in Alzheimer’s disease: current evidence, challenges, and future opportunities - Yan, Long; Li, Hong; Qian, Yulin; Liu, Qidi; Cong, Shan; Dou, Baomin; Wang, Yu; Wang, Meng; Yu, Tao (Frontiers in Neuroscience, 2024)
Alzheimer’s disease, one of the most severe and common neurodegenerative diseases, has no effective cure. Therefore it is crucial to explore novel and effective therapeutic targets. The gut microbiota - brain axis has been found to play a role in Alzheimer’s disease by regulating the neuro-immune and endocrine systems. At the same time, acupuncture can modulate the gut microbiota and may impact the course of Alzheimer’s disease. In this Review, we discuss recent studies on the role of acupuncture on the gut microbiota as well current challenges and future opportunities of acupuncture as potential treatment for the prevention and treatment of Alzheimer’s disease.